Vivências de pais e/ou cuidadores de crianças com autismo em um serviço de plantão psicológico - NOBRE, Diana da Silva (Universidade Federal da Bahia, 2023)
Objective: to reveal the experiences of parents and / or caregivers of children with autism in a Psychological Service. Method: a descriptive, qualitative study with phenomenological inspiration, carried out with six parents / guardians by a nongovernmental organization located in Belém, Pará, Brazil. An interview and the versions of meaning were used for data collection. After analyzing the convergent points present in the versions of meaning, the analysis of the data was performed through the formation of three themes of meanings. Results: There was a formation of three themes of meaning: “mourning due to the diagnosis of autism”; “Difficulties with childcare” and “social isolation”. Conclusion: the stories and needs that led parents and / or caregivers of the children with autism to seek psychological services present singularities, however mourning due to the diagnosis of autism, difficulties with childcare and social isolation were the commonly shared themes